I sing black feminism by Cida Souza - Paz, Vanessa Silva (2025)
It is a reflection on the poem I sing black feminism, by Cida Souza, a black writer from the city of Cardeal da Silva, Bahia, Brazil. We will discuss what her verses propose, considering the trajectory of black women in Brazil. In this sense, black feminism will be the guiding thread to think about the power of this rewriting, tagged by intersectional prejudices. For this reflection, studies by Santiago (2020), Anzaldúa (1980), Evaristo (2020), Zakaria (2020), Spivak (2010), Moore (2007), Moreira (2015, 2020), among others, will be considered. Therefore, we perceive how Cida Souza's poetics reveals itself as a force device pointing to a re-existence of oneself and other possible worlds.